(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
Argumentation is a type of discourse in which a speaker defends a claim in a discussion. The present work focuses on the argumentative complexity and the evaluative and evidential resources that characterize the disputes of children of different socioeconomic levels. We analyzed 94 disputes between 4-year-old children and other children (5 to 10 years old) in situations of spontaneous play registered in homes of middle and low socioeconomic status (SES). The analysis identified marginal differences in argumentative complexity between the groups. On the other hand, significant differences were found in evaluative expressions of emotion and in deontic and exclamatory evidential markers, more frequently used by the low SES group. The mid SES group tends to use a higher number of expressions of causality and connectors. The results are discussed with reference to the findings of previous research.